2022
DOI: 10.17219/acem/146321
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab in highly resistant acute gastrointestinal graft-versus-host disease after allogeneic stem cell transplantation: A single-center pediatric series

Abstract: Background. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a lifesaving procedure in malignant and nonmalignant diseases. However, it is associated with a considerable risk of graft-versus-host disease (GvHD). Steroids are a first-line therapy for acute GvHD (aGvHD), but there is no standard treatment for steroid-resistant (SR) gastrointestinal (GI) aGvHD, which has a poor prognosis. The anti-integrin antibody, vedolizumab, could help in controlling SR GI aGvHD symptoms by blocking lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In this study, only one patient had non‐GI manifestations, and all patients rapidly achieved durable clinical response and gradual histologic improvement. A similar response profile was reported in a few cases of pediatric patients published so far 10–13 . However, other case series that included adult patients with more severe disease, and with concurrent skin and liver involvement, showed less encouraging results 19,20 .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, only one patient had non‐GI manifestations, and all patients rapidly achieved durable clinical response and gradual histologic improvement. A similar response profile was reported in a few cases of pediatric patients published so far 10–13 . However, other case series that included adult patients with more severe disease, and with concurrent skin and liver involvement, showed less encouraging results 19,20 .…”
Section: Discussionsupporting
confidence: 79%
“…Evidence of safety and efficacy of this modality for treating GI GVHD in children is scarce with only one case report and three case series recently published. [10][11][12][13] In this study, we present our experience in treating thirteen pediatric patients with vedolizumab for GI aGVHD. Acute GVHD International Consortium (MAGIC) staging criteria.…”
Section: Stagementioning
confidence: 99%
See 2 more Smart Citations
“…Two of these patients experienced a complete response ( 115 ). Rosa et al reported 3 pediatric patients with oncological diseases and grade IV gut aGvHD, of whom only one achieved GvHD remission and Fukuta et al reported 1 patient with a clinical response to vedolizumab ( 116 , 117 ). Aldouby Bier reported on 13 pediatric patients with SR gut aGvHD treated with vedolizumab, among whom 8 presented a clinical recovery and 2 had ongoing chronic colitis.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%